Planning complementary conservation of crop wild relative diversity in southern Africa - Brehm, Joana Magos; Gaisberger, Hannes; Kell, Shelagh; Quijano, Mauricio Parra; Thormann, Imke; Dulloo, Mohammad Ehsan; Maxted, Nigel (Wiley, 2022)
Aim To identify priority areas for in situ conservation and collection of germplasm for ex situ backup of crop wild relative (CWR) diversity in the Southern African Development Community (SADC) region as part of an action plan for the conservation and use of the region's important CWR diversity.